2010
DOI: 10.1186/cc8941
|View full text |Cite
|
Sign up to set email alerts
|

Prospective monitoring of cefepime in intensive care unit adult patients

Abstract: IntroductionCefepime has been associated with a greater risk of mortality than other beta-lactams in patients treated for severe sepsis. Hypotheses for this failure include possible hidden side-effects (for example, neurological) or inappropriate pharmacokinetic/pharmacodynamic (PK/PD) parameters for bacteria with cefepime minimal inhibitory concentrations (MIC) at the highest limits of susceptibility (8 mg/l) or intermediate-resistance (16 mg/l) for pathogens such as Enterobacteriaceae, Pseudomonas aeruginosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
84
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 46 publications
3
84
0
2
Order By: Relevance
“…Several groups have shown the feasibility of b-lactam therapeutic drug monitoring in the general ICU population (27)(28)(29), and our data suggest that this monitoring may be particularly important in patients on CRRT. Our data suggest that a piperacillin dose of 9 g/d (piperacillin/tazobactam=3.375 g every 8 hours) may result in failure to reach the PD goal, and practitioners should consider using doses above 9 g/d in practice.…”
Section: Discussionmentioning
confidence: 61%
“…Several groups have shown the feasibility of b-lactam therapeutic drug monitoring in the general ICU population (27)(28)(29), and our data suggest that this monitoring may be particularly important in patients on CRRT. Our data suggest that a piperacillin dose of 9 g/d (piperacillin/tazobactam=3.375 g every 8 hours) may result in failure to reach the PD goal, and practitioners should consider using doses above 9 g/d in practice.…”
Section: Discussionmentioning
confidence: 61%
“…These previous studies lacked PK/PD data, which could be highly useful in interpreting observed outcomes. Very few studies have analyzed patient outcomes according to fT ϾMIC in cefepime-treated patients (12)(13)(14). As such, the necessary fT ϾMIC to prevent mortality for cefepime-treated patients with GNBSI is not well defined.…”
mentioning
confidence: 99%
“…19 Cefepime is a fourth-generation cephalosporin commonly used for nosocomial infections for which prolonged and continuous infusions have been evaluated. [20][21][22][23][24][25][26] The concern about achieving appropriate T > MIC with traditional dosage regimens (eg, 1-2 g every 8-12 hours infused over 30 minutes) for cefepime is similar to the concerns for piperacillin/tazobactam in critically ill patients at risk for resistant pathogens. [21][22][23][24][25] Data suggest prolonged or continuous infusion strategies may provide higher T > MIC and increase the probability that the infection will be resolved.…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…[20][21][22][23][24][25][26] The concern about achieving appropriate T > MIC with traditional dosage regimens (eg, 1-2 g every 8-12 hours infused over 30 minutes) for cefepime is similar to the concerns for piperacillin/tazobactam in critically ill patients at risk for resistant pathogens. [21][22][23][24][25] Data suggest prolonged or continuous infusion strategies may provide higher T > MIC and increase the probability that the infection will be resolved. 22,23,26 Changing the duration of infusion to 6 hours or administering a single 2000-mg loading dose followed by 24-hour continuous infusion of 4000 mg increases the probability of optimal T > MIC by 30% across different levels of renal function and pathogen MICs.…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%